Gold nanorod-based multifunctional nanocarrier for synergistic chemo-photothermal therapy in tumors. Issue 72 (11th December 2018) - Wang, Yi; Cui, Qiyao; Zhao, Xiaoshuang; Qin, Tang; Wang, Wenjing; Sun, Hongmei; Zhu, Hongda; Guo, Huiling; Sun, Honghao
Abstract : Synergistic photothermal therapy (PTT) and chemotherapy is an efficient strategy for tumor therapy. Abstract : Synergistic photothermal therapy (PTT) and chemotherapy is an efficient strategy for tumor therapy. However, it is still a challenge to design a smart delivery system able to release a drug at the appropriate time and site of action. Here, we have synthesized photosensitive molecule 7-(double dodecylamine)-4-hydroxymethylcoumarin which was introduced in a nanocarrier GNR@SiO2 -DOX@CouC12 -HA (GSDCH) to achieve manually controlled drug release. The specific nanocarrier was fabricated using a GNR core for photothermal therapy, a mesoporous silica shell for drug loading, and the coumarin moiety as a blocking agent and intelligent controlled switch. In addition, cellular uptake of GSDCH by HeLa cells can be achieved effectively with the help of hyaluronic acid (HA). Owing to the controlled and targeted drug release properties, the GSDCH with photothermal- and chemo-therapy showed significantly enhanced therapeutic efficiency for HeLa tumor-bearing mice compared to the results of single therapy alone. It indicated that the GSDCH had great potential in tumor therapy with negligible systematic toxicity.